Bis(acetone 4-phenyl-thio-semi-carbazonato-2 N 1,S)zinc(II) - Tan, Kong Wai; Ng, S.W.; Maah, Mohd Jamil; Ng, C.H. (International Union of Crystallography, 2009)
The ZnII atom in the title compound, [Zn(C10H 12N3S)2], is N,S-chelated by the deprotonated Schiff base in a tetra-hedral environment. The metal atom lies on a twofold rotation axis that relates one anion to the other. The amino H atom forms an intermolecular N - H⋯π inter-action to an aromatic ring. © 2009 Tan et al.